Bridging the Gap between Indian Urban Youth and Rural, Civic and Social Service Sector: A Collaborative Approach to Sustainable Development in Higher Education - Khurana, Neeta; Sharma, Dr.Ritu Sharma (Advances in Social Sciences Research Journal, 2017)
In the fast paced world of the urban set up, the youth in the cities is far removed from the concerns and realities of Rural India. The Internship Model proposed in the Higher Education segment which makes it mandatory for all technical students to undertake work with Non Government Organizations (NGO) helps bridge this gap. It provides an interface with society through social initiatives when young students align themselves with working with them thereby getting new and fresh perspectives and gain a deeper understanding of the environmental, social and economic issues from both an urban and rural perspective. Internship program is a pre-service training designed to render practical experience of a given job. For better execution of policies during one’s professional career, a technocrat is required to come to terms with the realities of life. The internships are designed to impart to students values and/or duties which include justice, freedom, equality, diversity, authority, privacy, participation, truth, patriotism, human rights, rule of law, tolerance, mutual assistance, self-restraint and self-respect. The Objectives of Rural, Civic Social Service Internships are to develop a holistic view of social work and social welfare in the community, with special emphasis on the role of different agencies like Govt. departments and NGOs in human services; to allow students to apply, evaluate, test and integrate academic knowledge and theoretical concepts in a work setting; to reduce intellectual and geographical parochialism of the students; to understand the NGO and other civic bodies and welfare agency as an organization, and understand its structure, functions, activities and sources of funding; to develop an understanding of the opportunities in working with diverse populations. The present paper is based on a study conducted on a group of 687 engineering students of First Year of Gujarat (Ahmedabad). Feedback from the students about the Internships and feedback of the coordinators from over 187 NGO’s, Government and Civic and Social Service organizations was taken to understand the reach out of the Urban Youth and the impact it had on their understanding of the people of rural India and the functioning of the NGO’s , Government and Civic bodies. The role of Higher Education to bridge the Gap is also discussed and analyzed. Findings of the survey and internship feedback reflected a high acceptance and a strong sense of sensitivity towards rural population and the amount of work that goes into making efforts to create a change for the betterment of less privileged people. The role of Higher Education in bridging this gap between Urban Youth and Rural population becomes significant as the future workforce is sensitized to the real India which dwells on the periphery of the Urban modern glitz of the smart cities hence leading to an assurance that this will lead to inclusivity and acceptance of people from all across the spectrum of Indian populace.